Metabolic Profile Variations along the Differentiation of Human-Induced Pluripotent Stem Cells to Dopaminergic Neurons - Emma Veronica Carsana; Matteo Audano; Silvia Breviario; Silvia Pedretti; Massimo Aureli; Giulia Lunghi; Nico Mitro (Biomedicines, 2022)
In recent years, the availability of induced pluripotent stem cell-based neuronal models has opened new perspectives on the study and therapy of neurological diseases such as Parkinson’s disease. In particular, P. Zhang set up a protocol to efficiently generate dopaminergic neurons from induced pluripotent stem cells. Although the differentiation process of these cells has been widely investigated, there is scant information related to the variation in metabolic features during the differentiation process of pluripotent stem cells to mature dopaminergic neurons. For this reason, we analysed the metabolic profile of induced pluripotent stem cells, neuronal precursors and mature neurons by liquid chromatography–tandem mass spectrometry. We found that induced pluripotent stem cells primarily rely on fatty acid beta-oxidation as a fuel source. Upon progression to neuronal progenitors, it was observed that cells began to shut down fatty acid β-oxidation and preferentially catabolised glucose, which is the principal source of energy in fully differentiated neurons. Interestingly, in neuronal precursors, we observed an increase in amino acids that are likely the result of increased uptake or synthesis, while in mature dopaminergic neurons, we also observed an augmented content of those amino acids needed for dopamine synthesis. In summary, our study highlights a metabolic rewiring occurring during the differentiation stages of dopaminergic neurons.